ANALISIS KUALITAS PELAYANAN PAJAK KENDARAAN BERMOTOR (PKB) DI UNIT PENGELOLA PENDAPATAN DAERAH (UPPD) SAMSAT KABUPATEN TANAH LAUT KALIMANTAN SELATAN - Surya Bintang Andreas Purba; Maya Sari Dewi (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2025)
This study aims to analyze the quality of Motor Vehicle Tax (PKB) services at the Regional Revenue Service Implementation Unit (UPPD) of the Tanah Laut Regency Samsat (Regional Revenue Service Unit), South Kalimantan, and examine how this quality contributes to increasing regional tax revenue. Quality public services are one of the main keys to improving taxpayer compliance and optimizing regional original revenue (PAD). The method used in this study is a mixed methods, namely a combination of qualitative and quantitative approaches. Primary data were obtained through observation, interviews with service officers, and distribution of questionnaires to taxpayers. Meanwhile, secondary data were in the form of supporting documents, such as the number of motor vehicles, tax revenue targets and realizations, and the Samsat organizational structure. The assessment of service quality was analyzed using five SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The results show that the service quality at the Tanah Laut UPPD Samsat is classified as good, indicated by tax realization achievements that exceeded targets for three consecutive years (2022–2024). The tangibles and reliability dimensions showed very satisfactory results, indicated by adequate service facilities and procedural accuracy. Responsiveness and assurance demonstrate a quick response and high public trust in officers. However, the empathy dimension still needs improvement, particularly in providing facilities for the elderly and people with disabilities. This study concludes that excellent service quality directly contributes to increased regional motor vehicle tax revenue. Recommendations focus on improving inclusive service facilities and ongoing public outreach to build a stronger culture of tax compliance.